2015
DOI: 10.1016/j.neuroimage.2015.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic structure of neuronal tracts from time-dependent diffusion

Abstract: Interpreting brain diffusion MRI measurements in terms of neuronal structure at a micrometer level is an exciting unresolved problem. Here we consider diffusion transverse to a bundle of fibers, and show theoretically, as well as using Monte Carlo simulations and measurements in a phantom made of parallel fibers mimicking axons, that the time dependent diffusion coefficient approaches its macroscopic limit slowly, in a (lnt)/t fashion. The logarithmic singularity arises due to short range disorder in the fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
479
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(509 citation statements)
references
References 60 publications
23
479
7
Order By: Relevance
“…The approach, as used here, also neatly avoids the need for any analytical model of tortuous extra-cellular diffusion for which only approximations are available (Burcaw et al, 2015). Given that these compartment models tend to overestimate key microstructure parameters such as the axon diameter , including the effects of these intractable parameters not only gives us clinically useful parameters, but may also improve the estimation of other microstructure indices.…”
Section: Discussionmentioning
confidence: 99%
“…The approach, as used here, also neatly avoids the need for any analytical model of tortuous extra-cellular diffusion for which only approximations are available (Burcaw et al, 2015). Given that these compartment models tend to overestimate key microstructure parameters such as the axon diameter , including the effects of these intractable parameters not only gives us clinically useful parameters, but may also improve the estimation of other microstructure indices.…”
Section: Discussionmentioning
confidence: 99%
“…Some OGSE studies have reported that, at frequencies below 400 Hz, the OG-measured extra-axonal diffusivity transverse to axons in white matter is linearly dependent on the frequency of the employed OGSE sequence [2], whereas state-of-the art multi-compartment models of white matter relying on PGSE or OGSE sequences usually assume a Gaussian diffusion in the extra-axonal space [3][4][5][6]. A theoretical explanation was given in Burcaw et al [7], where the observed frequency-dependence is interpreted as resulting from the extra-axonal 2D short-range disorder of axonal packings in the plane transverse to white matter fibers.…”
Section: Introductionmentioning
confidence: 99%
“…where t is the diffusion time, ω is the dual frequency and t c represents the time to diffuse across the correlation length l c of the packing geometry (l c closely follows the mean external radius r ext of the axon packing [7,8]). Similar to recent models accounting for extra-axonal time-dependence in the case of single diffusion encoding sequences [9], a multi-compartment model for cosine OGSE sequences was proposed in Ginsburger et al [10] which added a frequency-dependent term in the extra-axonal diffusion tensor perpendicular diffusivity based on Equation (2), showing a significant improvement of the model fit quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature is increasingly emphasizing the need for such a representation, where accounting for the diffusion time dependence of the extra-axonal diffusion signal [1,2] has already resulted in a more accurate estimation of the axon density and diameter [3]. To measure the four-dimensional dMRI signal it is necessary to go beyond a multi-shell q-space acquisition -which only varies gradient strength and direction -and also vary the diffusion time.…”
Section: Introductionmentioning
confidence: 99%